Social representations of sharks, perceived communality, and attitudinal and behavioral tendencies towards their conservation: an exploratory sequential mixed approach - Neves, João (2021)
Sharks are crucial to the marine ecosystem, but they are critically declining. Their bad public image explains, to some extent, the lesser concern for their conservation compared to other marine species. Extending previous research which has mainly focused on the study of attitudes towards sharks, we propose a two studies sequence, first by exploring the shark's social representation, followed by an exploration of some stereotypical traits that may affect attitudes toward shark conservation. Study 1 specifically exploreed the social representation of sharks in a sample of zoo goers (N = 979). Main results showed that the representation was ambivalent and participants considered sharks as human predators. Surprisingly, findings showed that sharks were also seen as highly agentic and little communal animals. Consequently, Study 2 (N = 60) was designed to more thoroughly explore this gendered view as well as its implications in the attitudes and behavioral intention towards shark conservation. Results showed that, although sharks were again perceived as highly agentic, it was the perception of the sharks' communality that was associated with more positive attitudes towards their conservation and a higher tendency to choose a shark conservation trust as first choice. Implications of studies 1 and 2 results for sharks' conservation communication strategies and policies are discussed.